Differential Effects of Early- and Late-Life Access to Carotenoids on Adult Immune Function and Ornamentation in Mallard Ducks (Anas platyrhynchos) - Butler, Michael W. (Public Library of Science, 2012)
Environmental conditions early in life can affect an organism’s phenotype at adulthood, which may be tuned to perform optimally in conditions that mimic those experienced during development (Environmental Matching hypothesis), or may be generally superior when conditions during development were of higher quality (Silver Spoon hypothesis). Here, we tested these hypotheses by examining how diet during development interacted with diet during adulthood to affect adult sexually selected ornamentation and immune function in male mallard ducks (Anas platyrhynchos). Mallards have yellow, carotenoid-pigmented beaks that are used in mate choice, and the degree of beak coloration has been linked to adult immune function. Using a 2×2 factorial experimental design, we reared mallards on diets containing either low or high levels of carotenoids (nutrients that cannot be synthesized de novo) throughout the period of growth, and then provided adults with one of these two diets while simultaneously quantifying beak coloration and response to a variety of immune challenges. We found that both developmental and adult carotenoid supplementation increased circulating carotenoid levels during dietary treatment, but that birds that received low-carotenoid diets during development maintained relatively higher circulating carotenoid levels during an adult immune challenge. Individuals that received low levels of carotenoids during development had larger phytohemagglutinin (PHA)-induced cutaneous immune responses at adulthood; however, dietary treatment during development and adulthood did not affect antibody response to a novel antigen, nitric oxide production, natural antibody levels, hemolytic capacity of the plasma, or beak coloration. However, beak coloration prior to immune challenges positively predicted PHA response, and strong PHA responses were correlated with losses in carotenoid-pigmented coloration. In sum, we did not find consistent support for either the Environmental Matching or Silver Spoon hypotheses. We then describe a new hypothesis that should be tested in future studies examining developmental plasticity.